Digital Architecture for Public Space Design at Sineleyan Lake Using a Water Analogy - Defie Ronald Wawointana; Jefri Muhaling; Iwan Ponengo (Journal of Technology and Engineering, 2026)
Sineleyan Lake is one of Tomohon City’s natural assets with strategic potential as an urban public space and tourism destination supporting the Tournament of Flowers (ToF). Located in the city center, the lake has important ecological, visual, and recreational value but faces environmental challenges, including sedimentation, inadequate drainage, poor maintenance, and waste disposal. This study aims to develop a public space design for the Sineleyan Lake area by integrating digital architecture with a water analogy concept. A qualitative-exploratory architectural design research approach was employed, including site identification, contextual analysis, concept development, site planning, massing exploration, and digital visualization. The water analogy was translated into three design principles: flexibility, dynamic-static character, and transparency, which guided the development of adaptive building forms, spatial organization, and visual connections between buildings, open spaces, and the lake. The proposed design covers approximately 12,000 m² and consists of reception, management, recreation, and green open space zones. The novelty of this study lies in integrating digital architecture as a design methodology with the water analogy concept to create a context-responsive lakefront public space. This integration enables systematic form exploration, adaptive spatial planning, and digital visualization while reflecting the ecological and visual characteristics of the site. The study contributes a contextual design framework for sustainable waterfront public space development that may serve as a reference for similar urban lake revitalization projects in Indonesia.